Door-to-Door Strategy of PDI-Perjuangan’s in winning the Majority of Regional People’s Representative Council Seats in Central Java Province in the 2019 Election - Alrizoma Akrom; Guntur F. Prisanto; Poppy Ruliana (Institute of Computer Science (IOCS), 2021)
This study analyzes the PDI-Perjuangan door-to-door strategy in winning the majority of seats in the Central Java Provincial DPRD in the 2019 general election (election). to- door PDI-Perjuangan. The researcher uses a qualitative approach with the case study method, with data collected through in-depth interviews and literature study. The conceptual framework for the political communication strategy, especially the door-to- door strategy, was used by researchers to analyze the strategy implemented by the PDI- Perjuangan Central Java in the 2019 election. The discussion in this study found several things, namely: First, there are three important things used in the strategy PDI-P political communication: maximizing the entire structure of the party, the party wing, and maximizing the role of the community, volunteers to professional and hobby groups. Second, so far, political parties have worked on the network/engineering of the party's structure. The PDI-P Central Java's Door To Door Campaign (DTDC) team named the Gorong-Gorong Juang (GGJ) team worked outside the party machine. In its campaign work, the GGJ Team is oriented towards involving people living in the intervention target areas. Third, maximizing the door-to-door strategy succeeded in winning the majority of seats in the Central Java Provincial DPRD in the 2019 election. A very significant increase in the number of seats, although not all areas were intervened by DTDC